Parental Stress and Satisfaction in Parents With Pre-school and School Age Children - Oyarzún-Farías, María de los Angeles; Cova, Félix; Bustos Navarrete, Claudio (Frontiers in Psychology, 2021)
Parenting is a transforming experience for the life of parents that brings joy and satisfaction as well as challenges, frustration, and demands. The aim of this study was to determine the relationship between ‘parental stress and satisfaction’ and work-home conflict, perceived social support, and global satisfaction with life, and to determine the moderating role of the parent's gender. A sample of 244 participants was studied: 49.6% (121) mothers and 50.4% (123) fathers with children between 2 and 12 years of age. The data was analysed by means of multiple linear regression models and Beta regression for stress and parental satisfaction, respectively, and they were complemented with general and conditional dominance analyses to estimate the relevance of the predictors. Mothers presented higher levels of parental stress and satisfaction than fathers. Being female, having two children, and home-work conflict were predictors of a higher parental stress. Age was also a predictor, as younger parents and also those older than 37 years of age showed more parental stress. Having no partner and being male was associated to lower parental satisfaction. In conclusion, parental stress and satisfaction emerge as clearly differentiated dimensions of parenting experience. The gender gap in parental stress could be linked to the persistence of traditional roles regarding the care of the children, in agreement with the findings in other research.